Carbon glue powder modified ion battery negative electrode material and preparation method thereof

Optimizing the surface chemical composition and microstructure of waste rubber carbon materials through the gas-phase-solid phase crosslinking modification method, solving the problem that sulfur groups affect the charge and discharge efficiency and the structure is not suitable for alkali metal ion storage, and achieving efficient energy storage performance improvement .

CN119143113BActive Publication Date: 2025-02-18ZHEJIANG BAYONG NEW MATERIAL TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411612010.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

When the waste rubber material is converted into carbon material, the presence of sulfur groups reduces the first charge and discharge efficiency, and the irregular microcrystalline structure and pore structure of the material are not conducive to the storage of alkali metal ions, resulting in a lower battery capacity.

Method used

The gas-phase-solid phase crosslinking modification method is used to optimize the surface chemical composition and microstructure of rubber carbon materials through anhydrous ethanol cleaning and alcohol mixing treatment, combined with pyrolysis and acid solution soaking.

Benefits of technology

It significantly improves the first Coulomb efficiency and structural stability of the negative electrode material of rubber carbon battery, improves the order and pore structure of the microcrystalline structure, and improves energy storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143113B_ABST
    Figure CN119143113B_ABST
Patent Text Reader

Abstract

The present invention provides a carbon rubber powder modified ion battery negative electrode material and a preparation method thereof, using waste rubber as a raw material, in-situ sulfur doping of the waste rubber during the carbonization process, and then further using a gas-phase-solid-phase crosslinking modification method to modify the rubber powder carbon material during the heat treatment process, so as to improve the first coulomb efficiency of the waste rubber powder carbon material, and optimize the crystallite and pore structure to adapt to the storage of alkali metal ions. The present invention reduces the surface sulfur groups of the waste rubber powder carbon material, and improves the carbon oxygen group composition on the surface of the carbon material, thereby reducing the occurrence of side reactions during the first charge and discharge process. At the same time, it can also improve the orderliness and pore structure of the carbon crystallites on the surface of the material, further improving its first coulomb efficiency and energy storage performance. The present invention provides a new option for the high added value recycling of waste rubber materials, and at the same time has an important role in promoting the development of negative electrode materials for sodium ion batteries and the practical application of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a carbon glue powder modified ion battery negative electrode material and a preparation method thereof. Background Art

[0002] The reuse of waste rubber materials, especially converting them into high-performance sodium ion batteries (SIBs) anode materials, is of great significance for alleviating environmental pressure and promoting the development of sustainable energy. However, the reuse of waste rubber materials faces many technical difficulties, such as interference from impurity elements and mismatch of intrinsic microstructure of materials.

[0003] During the rubber manufacturing process, excessive sulfur is added to enhance its structural stability and mechanical properties. During the conversion of waste rubber into carbon materials, sulfur elements are retained, especially sulfur groups are formed on the surface of carbon materials. These sulfur groups react with the electrolyte during the first charge and discharge process, consuming a large amount of electrolyte and forming a solid electrolyte interface (SEI), which significantly reduces the first coulomb efficiency (ICE) and affects the overall performance of the battery.

[0004] In addition, directly carbonized rubber carbon materials usually have irregular microcrystalline and pore structures, which limits their application as SIBs anode materials because such structures are not conducive to the effective storage of alkali metal ions, resulting in low battery capacity. Therefore, developing an effective method to improve the first coulombic efficiency of carbon materials converted from waste rubber and optimize their microcrystalline and pore structures is crucial to improving the performance of SIBs anode materials. Summary of the invention

[0005] The purpose of the embodiment of the present invention is to provide a method for preparing a carbon rubber powder modified ion battery negative electrode material, which effectively improves the first coulombic efficiency and structural stability of the rubber carbon battery negative electrode material by optimizing the surface chemical composition and microstructure of the waste rubber derived carbon material.

[0006] The second purpose of the embodiment of the present invention is to provide a carbon glue powder modified ion battery negative electrode material.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is a method for preparing a carbon glue powder modified ion battery negative electrode material, comprising the following steps:

[0008] S1. Wash and dry the rubber particles using anhydrous ethanol;

[0009] S2, mixing the rubber particles obtained after washing with alcohols and stirring them thoroughly;

[0010] S3, pyrolyzing the mixture obtained in S2 in an inert gas atmosphere, and then cooling to room temperature;

[0011] S4, grinding and screening the product obtained in S3, then soaking it in water or acid solution, stirring it, filtering to remove the upper layer of liquid, and then washing it with neutral water and drying it;

[0012] S5, pyrolyzing the product obtained in S4 at high temperature in an inert gas atmosphere, adding a mixture of one or more of ethanol, ethylene glycol, and propylene glycol at the air inlet, and cooling to room temperature;

[0013] S6. Cool the product of S5 to room temperature and then grind and screen to obtain the negative electrode material for the ion battery.

[0014] Furthermore, the alcohols in S2 include one or more combinations of ethanol, ethylene glycol, glycerol, and propylene glycol.

[0015] Furthermore, the mass ratio of the rubber particles to the alcohol in S2 is 1:(0.1-2).

[0016] Furthermore, the pyrolysis temperature in S3 is 200-500° C.; the flow rate of the inert atmosphere is 0-200 mL / min, and the pyrolysis time is 2-3 h.

[0017] Furthermore, in S4, the product obtained in S3 is ground and screened to 50-100 mesh; and in S6, the product obtained in S5 is ground and screened to 200-300 mesh.

[0018] Furthermore, the acid solution in S4 includes one or more mixtures of 1-2 mol / L hydrochloric acid solution, sulfuric acid solution, and nitric acid solution; and the soaking time in water or acid solution is 2-3 hours.

[0019] Furthermore, the temperature of high temperature pyrolysis in S5 is 600-1600°C; and the flow rate of the inert atmosphere is 50-200 mL / min.

[0020] The battery negative electrode material is prepared by the preparation method as described above.

[0021] Compared with the prior art, the beneficial effects of the present invention include at least the following points:

[0022] 1. The present invention effectively reduces the sulfur group content on the surface of the waste rubber carbon material through the gas phase-solid phase crosslinking modification method, thereby significantly reducing the occurrence of side reactions during the first charge and discharge process and improving the first charge and discharge efficiency.

[0023] 2. The present invention can also improve the orderliness of the microcrystalline structure and the pore structure of the waste rubber carbon material, making the material more suitable for the storage of alkali metal ions, thereby improving the energy storage performance.

[0024] 3. The present invention provides a high value-added recycling approach for waste rubber materials, which not only improves the utilization rate of waste rubber, but also helps to reduce environmental pollution and resource waste, and promotes the development of a circular economy.

[0025] 4. The present invention improves the first coulombic efficiency and overall performance of waste rubber carbon materials, thereby providing new ideas and technical support for the research and development of negative electrode materials for sodium ion batteries, and is helpful to promote the practical application and development of sodium ion battery technology.

[0026] In summary, the present invention not only improves the first coulombic efficiency of waste rubber carbon materials, but also optimizes their microcrystal and pore structure, thereby significantly improving the application value of waste rubber in SIBs negative electrode materials. This innovative treatment method has opened up a new path for the environmentally friendly reuse of waste rubber, which is of great significance for promoting sustainable development and circular economy. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 is a TEM image of the waste rubber-based carbon material prepared in Example 1;

[0029] Figure 2 is the N2 adsorption / desorption isotherm of the waste rubber-based carbon material prepared in Example 1;

[0030] Figure 3 is the pore size distribution curve of the waste rubber-based carbon material prepared in Example 1;

[0031] Figure 4 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Example 1 at a current density of 0.1 C;

[0032] Figure 5 This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Example 1 at a current density of 0.1 C;

[0033] Figure 6 This is a rate performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Example 1;

[0034] Figure 7 is the Raman spectrum of the waste rubber-based carbon material prepared in Example 1;

[0035] Figure 8 is the XRD spectrum of the waste rubber-based carbon material prepared in Example 1;

[0036] Fig. 9 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 3 at a current density of 0.1 C;

[0037] Fig.10 This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 3 at a current density of 0.1 C;

[0038] Fig.11 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 5 at a current density of 0.1 C;

[0039] Fig.12 This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 5 at a current density of 0.1 C;

[0040] Fig.13 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 4 at a current density of 0.1 C;

[0041] Fig.14 This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 4 at a current density of 0.1 C;

[0042] Fig.15 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Example 10 at a current density of 0.1 C;

[0043] Fig.16 is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Example 10 at a current density of 0.1 C;

[0044] Fig.17 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 2 at a current density of 0.1 C;

[0045] Fig.18 This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 2 at a current density of 0.1 C;

[0046] Fig.19 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 6 at a current density of 0.1 C;

[0047] Fig. 20This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 6 at a current density of 0.1 C;

[0048] Fig.21 is a TEM image of the waste rubber-based carbon material prepared in Comparative Example 1;

[0049] Fig. 22 This is the XRD spectrum of the waste rubber-based carbon material prepared in Comparative Example 1;

[0050] Fig.23 is the Raman spectrum of the waste rubber-based carbon material prepared in Comparative Example 1;

[0051] Fig.24 is the N2 adsorption / desorption isotherm curve of the waste rubber-based carbon material prepared in Comparative Example 1;

[0052] Fig.25 is the pore size distribution curve of the waste rubber-based carbon material prepared in Comparative Example 1;

[0053] Fig.26 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 1 at a current density of 0.1 C;

[0054] Fig. 27 This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 1 at a current density of 0.1 C;

[0055] Fig.28 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 7 at a current density of 0.1 C;

[0056] Fig.29 This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 7 at a current density of 0.1 C;

[0057] Fig.30 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 8 at a current density of 0.1 C;

[0058] Fig.31 This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 8 at a current density of 0.1 C;

[0059] Fig.32 This is the first cycle charge and discharge curve of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Comparative Example 9 at a current density of 0.1 C;

[0060] Fig.33This is a cycle performance diagram of a sodium ion battery assembled from waste rubber-based carbon materials prepared in Example 9 at a current density of 0.1 C. DETAILED DESCRIPTION

[0061] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] This embodiment provides a carbon glue powder modified ion battery negative electrode material, and the preparation method of the ion battery negative electrode material is as follows:

[0063] S1: Use anhydrous ethanol to preliminarily clean the rubber particles and dry them;

[0064] In this embodiment, the source of the rubber particles includes but is not limited to waste tires and other waste rubber products.

[0065] S2: mixing the rubber particles with one or more of ethanol, ethylene glycol, glycerol, and propylene glycol in a mass ratio of 1:(0.1-2), stirring thoroughly, and obtaining a mixture;

[0066] S3: pre-pyrolyze the mixture at 200-500°C for 2-3h, with the pyrolysis atmosphere being nitrogen or argon or a mixture of the two, at a flow rate of 0-200 mL / min, and cool to room temperature to obtain product A;

[0067] S4: grinding product A to 50-100 mesh, soaking in water or one or more of 1-2 mol / L acid solution, stirring, filtering and removing the upper layer liquid to obtain product B;

[0068] In this embodiment, the acid solution includes one or more combinations of hydrochloric acid, sulfuric acid, and nitric acid solutions;

[0069] S5: washing the product B with water until it is neutral and drying it to obtain the product C;

[0070] S6: pyrolyze the product C at 600-1600℃ for 2-3h. The pyrolysis atmosphere is nitrogen or argon or a mixture of the two in any ratio. One or more of ethanol, ethylene glycol, and propylene glycol are added to the air inlet for mixing at a flow rate of 50-200 mL / min. After cooling to room temperature, the final product D is obtained.

[0071] In this embodiment, the ethanol, ethylene glycol, glycerol, and propylene glycol used in S2 and S6 are all solutions with a mass fraction of 95%; during the process of inert gas introduction, they are bubbled into gas and then brought into the reaction system.

[0072] S7: Grind and sieve the product D to 200-300 meshes to obtain the negative electrode material for the ion battery.

[0073] Existing methods usually use solvent liquid phase or heat treatment to modify the rubber carbon material, because the solvent phase and heat treatment are relatively simple and clear in direction for regulating the surface element groups of the rubber carbon material and the conversion of microcrystals and pore structures; compared with other rubber carbon materials (such as asphalt carbon, biomass carbon), the rubber carbon itself has a complex type and composition, and its carbon material composition is relatively loose. Traditional methods for pore structure regulation (such as template method) are not applicable. At the same time, because the type and composition of rubber carbon are complex, the microscopic composition changes produced during the regulation process are more difficult to control. The present embodiment adopts a gas-solid phase crosslinking modification method to regulate the surface element groups of the rubber carbon material and the conversion of microcrystals and pore structures. However, gas-solid phase crosslinking is difficult to control during the high-temperature thermal conversion of the rubber carbon material. Taking carbon-oxygen functional groups as an example, the types and proportions of C=O, CO, etc. obtained under different experimental conditions and treatment methods (such as gas phase type, flow rate, secondary pyrolysis temperature, etc.) are all different, and there is no obvious regularity. The present embodiment regulates the surface element groups of the rubber carbon material and the conversion of microcrystals and pore structures to eliminate the defects that are difficult to overcome by traditional methods.

[0074] Example 1

[0075] S1: Use anhydrous ethanol to preliminarily clean the rubber particles and dry them;

[0076] S2: mixing the rubber powder and propylene glycol in a mass ratio of 1:1, and stirring thoroughly to obtain a mixture;

[0077] S3: pre-pyrolyze the above mixture at 400 °C, with argon as the pyrolysis atmosphere and a flow rate of 50 mL / min, and cool to room temperature to obtain product A;

[0078] S5: washing the product B with water until it is neutral and drying it to obtain the product C;

[0079] S4: Grind product A to 100 mesh, soak it in 1 mol / L nitric acid and sulfuric acid in a volume ratio of 1:1 for 2 h, stir, and filter to remove the upper liquid to obtain product B;

[0080] S6: The product C was pyrolyzed at 900°C in an argon atmosphere, and ethylene glycol was added at the gas inlet at a flow rate of 50 mL / min. The final product D was obtained after cooling to room temperature.

[0081] S7: Grind and sieve the product D to 200-300 meshes to obtain the negative electrode material for the ion battery.

[0082] In this embodiment, the temperature is properly controlled and the pyrolysis atmosphere is reasonable, so that the carbon material is fully gas-solid cross-linked and a better microstructure is obtained. As shown in the figure, Figure 1 The TEM images show that the edges of carbon materials have more ordered structures. Figure 2 In the low-pressure region of the isothermal adsorption curve shown in FIG, a significant and rapid increase in gas adsorption can be observed due to the micropore filling effect; combined with Figure 3 It can be found that the sample has a microporous structure at about 2 nanometers, which is consistent with Figure 2 The adsorption behavior is consistent with that shown in Figure 2 and Figure 3 The information can clearly infer that the sample has rich microporous structural characteristics, and its pore size distribution is concentrated around 2 nanometers, showing typical microporous material characteristics. Figure 4 , Figure 5 , Figure 6 The better performance shown in Figure 7 The material has obvious d peak and g peak. Figure 8 A relatively obvious broad diffraction peak appears at around 21°~27°, which corresponds to the (002) diffraction peak of carbon material. Such a broad diffraction peak indicates that the samples have obvious amorphous carbon structure.

[0083] Example 2

[0084] S1: Use anhydrous ethanol to preliminarily clean the rubber particles and dry them;

[0085] S2: mixing the rubber powder and ethylene glycol in a mass ratio of 1:1, stirring thoroughly to obtain a mixture;

[0086] S3: pre-pyrolyze the above mixture at 200°C, with argon as the pyrolysis atmosphere and a flow rate of 100 mL / min, and cool to room temperature to obtain product A;

[0087] S4: Grind product A to 50 mesh, soak in 1.5 mol / L hydrochloric acid for 2.5 h, stir, and filter to remove the upper liquid to obtain product B;

[0088] S5: washing the product B with water until it is neutral and drying it to obtain the product C;

[0089] S6: The product C was pyrolyzed at 900°C in an argon atmosphere, and ethylene glycol was added at the gas inlet at a flow rate of 100 mL / min. The final product D was obtained after cooling to room temperature.

[0090] S7: Grind and sieve the product D to 200-300 meshes to obtain the negative electrode material for the ion battery.

[0091] Example 3

[0092] A method for preparing a carbon glue powder modified ion battery negative electrode material comprises the following steps:

[0093] S1: Use anhydrous ethanol to preliminarily clean the rubber particles and dry them;

[0094] S2: mixing the rubber powder with a mixed solution of propylene glycol and ethylene glycol (mass ratio 1:1) in a mass ratio of 1:2, and stirring thoroughly to obtain a mixture;

[0095] S3: pre-pyrolyze the above mixture at 300°C, with argon as the pyrolysis atmosphere and a flow rate of 200 mL / min, and cool to room temperature to obtain product A;

[0096] S4: Grind product A to 70 mesh, soak in 1 mol / L sulfuric acid for 3 h, stir, and filter to remove the upper liquid to obtain product B;

[0097] S5: washing the product B with water until it is neutral and drying it to obtain the product C;

[0098] S6: The product C was pyrolyzed at 900°C in an argon atmosphere, and a mixed solution of propylene glycol and ethylene glycol (mass ratio 1:1) was added at the gas inlet at a flow rate of 200 mL / min. After cooling to room temperature, the final product D was obtained.

[0099] S7: Grind and sieve the product D to 200-300 meshes to obtain the negative electrode material for the ion battery.

[0100] Example 4

[0101] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S6 the pyrolysis atmosphere is argon and ethanol is added at the air inlet; the remaining steps are the same as those in Example 1.

[0102] Example 5

[0103] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S2, the glue powder and ethylene glycol are mixed in a mass ratio of 1:0.1 and fully stirred to obtain a mixture; the remaining steps are the same as those in Example 1.

[0104] Example 6

[0105] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S6 the pyrolysis atmosphere is argon and propylene glycol is added at the air inlet; the remaining steps are the same as those in Example 3.

[0106] Example 7

[0107] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S6, the pyrolysis atmosphere is argon gas, and a mixed solution of ethanol and propylene glycol (mass ratio 1:1) is added to the air inlet; the remaining steps are the same as those in Example 1.

[0108] Example 8

[0109] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the mixture is pre-pyrolyzed at 500°C in step S3, the pyrolysis atmosphere is argon, the flow rate is 50 mL / min, and the product A is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0110] Example 9

[0111] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S4, product A is ground to 100 mesh, soaked in nitric acid, stirred, centrifuged, and the upper liquid is removed to obtain product B; the remaining steps are the same as those in Example 1.

[0112] Example 10

[0113] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S4, product A is ground to 100 mesh, soaked in hydrochloric acid, stirred, centrifuged, and the upper liquid is removed to obtain product B; the remaining steps are the same as those in Example 1.

[0114] After pre-pyrolysis, hydrochloric acid is used for further surface modification and removal of soluble matter, making the surface groups of the material more uniform and improving the material performance relatively. Fig.15 and Fig.16 shown.

[0115] Embodiment 11

[0116] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the product C is pyrolyzed at 600°C in step S6, the pyrolysis atmosphere is argon gas, the flow rate is 50 mL / min, and the final product D is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0117] Example 12

[0118] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the product C is pyrolyzed at 1200°C in step S6, the pyrolysis atmosphere is argon, the flow rate is 100 mL / min, and the final product D is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0119] Embodiment 13

[0120] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the product C is pyrolyzed at 1600°C in step S6, the pyrolysis atmosphere is a mixture of argon and nitrogen, the flow rate is 150 mL / min, and the final product D is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0121] Embodiment 14

[0122] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the mixture is pre-pyrolyzed at 400°C in step S3, the pyrolysis atmosphere is argon, the flow rate is 0 mL / min, and the product A is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0123] Embodiment 15

[0124] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the mixture is pre-pyrolyzed at 400°C in step S3, the pyrolysis atmosphere is argon, the flow rate is 200 mL / min, and the product A is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0125] Example 16

[0126] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the product C is pyrolyzed at 900°C in step S6, the pyrolysis atmosphere is argon, the flow rate is 200 mL / min, and the final product D is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0127] Embodiment 17

[0128] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the mixture is pre-pyrolyzed at 300°C in step S3, the pyrolysis atmosphere is argon, the flow rate is 100 mL / min, and the product A is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0129] Embodiment 18

[0130] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S2, the glue powder and ethylene glycol are mixed in a mass ratio of 1:0.5 and fully stirred to obtain a mixture; the remaining steps are the same as those in Example 1.

[0131] Embodiment 19

[0132] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S2, the glue powder is mixed with a mixture of ethanol, ethylene glycol, glycerol and propylene glycol (the mass ratio of ethanol, ethylene glycol, glycerol and propylene glycol is 1:1:1:1) in a mass ratio of 1:1.5 and fully stirred to obtain a mixture; the remaining steps are the same as those in Example 1.

[0133] Embodiment 20

[0134] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the product C is pyrolyzed at 1400°C in step S6, the pyrolysis atmosphere is argon gas, the flow rate is 50 mL / min, and the final product D is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0135] Embodiment 21

[0136] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that step S4 uses water for soaking, the remaining steps are the same as those in Example 1.

[0137] Embodiment 22

[0138] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that the sulfuric acid concentration in step S4 is 2 mol / L, the remaining steps are the same as those in Example 1.

[0139] Comparative Example 1

[0140] S1: Use ethanol to preliminarily clean the rubber particles and dry them;

[0141] S2: pyrolysis of rubber particles at 900 °C in an argon atmosphere at a flow rate of 50 mL / min, and the final product was obtained after cooling to room temperature;

[0142] S3: Grind and sieve the product to 200-300 meshes to obtain the negative electrode material for the ion battery.

[0143] The surface of carbon materials prepared by direct carbonization method is rich in sulfur groups, and its carbon microcrystalline structure contains a large number of disordered regions, such as Fig.21 shown. Fig. 22 and Fig.23 It also shows that the material contains a highly disordered microcrystalline structure. Fig.24 and Fig.25 As shown in Figure 2, the pore structure of this material is mainly mesoporous, which gives the material a high specific surface area. However, these characteristics work together to negatively affect the actual electrochemical performance of the battery, resulting in poor performance, such as Fig.26 and Fig. 27 shown.

[0144] Comparative Example 2

[0145] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the product C is pyrolyzed at 1800°C in step S6, the pyrolysis atmosphere is argon gas, the flow rate is 50 mL / min, and the final product D is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0146] Although a higher secondary pyrolysis temperature can make the groups on the surface of the material more uniform, it will also reduce the distance between the carbon layers in the material, thus affecting its storage performance. Fig.17 and Fig.18 As shown, the end result is a degradation of the material's performance.

[0147] Comparative Example 3

[0148] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S6 the pyrolysis atmosphere is argon and propylene glycol is added at the air inlet; the remaining steps are the same as those in Example 2.

[0149] Ethylene glycol and propylene glycol not only have different melting points and boiling points, but also different molecular structures, which leads to different carbon microcrystal structures when they are cross-linked with rubber powder in the gas-solid phase during pyrolysis. Since propylene glycol has a higher boiling point and a larger molecular weight, it is more difficult to gasify during pyrolysis, resulting in poor cross-linking of carbon microcrystals, which leads to the following problems: Fig. 9 and Fig.10 The electrochemical performance shown is poor, but adding glycerol to S2 does not cause similar problems.

[0150] Comparative Example 4

[0151] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S3, the mixture is pre-pyrolyzed at 100°C, the pyrolysis atmosphere is argon, the flow rate is 100 mL / min, and the product A is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0152] When the pre-pyrolysis temperature is low, the cross-linking degree between materials will be insufficient, thus affecting their structural stability and electrochemical performance; Fig.13 and Fig.14 As shown, in the first charge and discharge cycle and long-term cycle stability test, the sodium ion battery prepared under this condition exhibited poor electrochemical performance.

[0153] Comparative Example 5

[0154] A method for preparing a carbon glue powder modified ion battery negative electrode material, except that in step S2, the glue powder and propylene glycol are mixed in a mass ratio of 1:2.5 and fully stirred to obtain a mixture; the remaining steps are the same as those in Example 1.

[0155] In the pre-pyrolysis stage, if the rubber powder is mixed with an excess of glycerol, the active groups on the solid surface will tend to be saturated during the subsequent pyrolysis process. Due to the excess of glycerol, its further modification effect becomes limited, so compared with Example 1, the performance improvement under this condition is not obvious. Fig.11 and Fig.12 The specific performance of this embodiment is demonstrated.

[0156] Comparative Example 6

[0157] A method for preparing a carbon glue powder modified negative electrode material for an ion battery, wherein the product C is pyrolyzed at 900°C in step S6, the pyrolysis atmosphere is argon, the flow rate is 0 mL / min, and the final product D is obtained after cooling to room temperature; the remaining steps are the same as those in Example 1.

[0158] Under the condition of no flow rate in the atmosphere, the hydrocarbon gas generated during the high-temperature pyrolysis of the material is difficult to be effectively removed, which prompts these gaseous products to undergo secondary cracking reactions. In this case, the surface structure of the material becomes more disordered, resulting in Fig.19 and Fig. 20 As shown, this leads to a decrease in material performance.

[0159] Comparative Example 7

[0160] S3 and S6 were pyrolyzed in air atmosphere; the remaining steps were the same as those in Example 1.

[0161] If air rather than inert gas is used as the pyrolysis atmosphere in steps S3 and S6, the carbon component in the material will undergo a violent oxidation reaction with oxygen under high temperature conditions, resulting in combustion of the material. This process will not only significantly reduce the yield of the target product, but also destroy the structural integrity of the material due to the unexpected oxidation loss of the carbon component, thereby affecting the electrochemical performance of the resulting material. Fig.28 , Fig.29 , which is manifested in the decrease of specific capacity shown in the first charge and discharge curve, and the unstable performance in the cycle performance test. In addition, such conditions will increase the safety risks during operation, because the oxidation reaction at high temperature is difficult to control and may cause safety accidents.

[0162] Comparative Example 8

[0163] S2 is not performed, and the remaining steps are the same as those in Example 1.

[0164] If glycerol and rubber powder are not mixed in a mass ratio of 1:1 and stirred thoroughly to form a cross-linked structure, the precursor will lack the necessary cross-linking effect, thus affecting the microstructure and mechanical stability of the material during the subsequent pyrolysis process. In this case, the pore distribution and conductive network of the obtained material will not be optimized. Fig.30 , Fig.31 , which ultimately affects the electrochemical performance as a negative electrode material for sodium ion batteries, manifested as lower capacity retention and poor cycle stability.

[0165] Comparative Example 9

[0166] No grinding or screening is performed in S4 and S7. The remaining steps are the same as those in Example 1.

[0167] Without grinding and screening, the resulting material will have a larger particle size and uneven particle size distribution. This will directly affect the surface area and active site distribution of the material, and thus affect its electrochemical performance as anode material for sodium ion batteries. Specifically, larger particle size and uneven particle size distribution may hinder the penetration of electrolytes, increase the length of ion transport paths, and reduce electrode utilization, such as Fig.32 , Fig.33 , ultimately leading to lower specific capacity and poor rate performance and cycling stability.

[0168] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0169] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon glue powder modified ion battery negative electrode material, characterized in that: The following steps are involved: S1. Wash and dry the rubber particles using anhydrous ethanol; S2, mixing the rubber particles obtained after washing with alcohols and stirring them thoroughly; The alcohol includes one or more combinations of ethanol, ethylene glycol, glycerol, and propylene glycol, and the mass ratio of the rubber particles to the alcohol is 1:(0.1-2); S3, pyrolyzing the mixture obtained in S2 in an inert gas atmosphere, and then cooling to room temperature; The pyrolysis temperature is 200-500°C; the flow rate of the inert atmosphere is 0-200 mL / min, and the pyrolysis time is 2-3h; S4, grinding and screening the product obtained in S3, then soaking it in water or acid solution, stirring it, filtering to remove the upper layer of liquid, and then washing it with neutral water and drying it; S5, pyrolyzing the product obtained in S4 at high temperature in an inert gas atmosphere, adding a mixture of one or more of ethanol, ethylene glycol, and propylene glycol at the air inlet, and cooling to room temperature; The temperature of high temperature pyrolysis is 600-1600°C; the flow rate of inert atmosphere is 50-200 mL / min, and the high temperature pyrolysis time is 2-3h; S6. Cool the product of S5 to room temperature and then grind and screen to obtain the negative electrode material for the ion battery.

2. The method for preparing a carbon glue powder modified ion battery negative electrode material according to claim 1, characterized in that: In S4, the product obtained in S3 is ground and screened to 50-100 mesh; and in S6, the product obtained in S5 is ground and screened to 200-300 mesh.

3. The method for preparing a carbon glue powder modified ion battery negative electrode material according to claim 1, characterized in that: The acid solution in S4 includes one or more mixtures of 1-2 mol / L hydrochloric acid solution, sulfuric acid solution, and nitric acid solution; the soaking time in water or acid solution is 2-3 hours.

4. A battery negative electrode material prepared by the method for preparing a carbon glue powder modified ion battery negative electrode material as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Preparation method of graphene coated biomass carbon negative material

    CN109950539A

  • Waste tire pyrolytic carbon catalyst, preparation method and application

    CN114045523A